Corporate Governance, Enterprise Risk Management, and Company Performance - Hidayah, Retnoningrum; Faizah, Siti Nurul; Sukirman, Sukirman; Suryandari, Dhini; Zahid, Anwar (Universitas Negeri Semarang, 2021)
This research aims to examine the effect of good corporate governance as measured by the board of directors, audit committee, and institutional ownership on company performance with enterprise risk management as an intervening variable. The population is LQ-45 companies listed in the Indonesia Stock Exchange (BEI). The hypothesis testing is using path analysis by IBM SPSS Statistics 21 software. The results shows the board of directors has a negative effect on the company performance. The audit committees and institutional ownership have no effect on the company performance. Enterprise risk management has a positive effect on the company performance. The board of directors, audit committees, and institutional ownership have a positive effect on the enterprise risk management. This research also shows that enterprise risk management able to mediate the effect of the board of directors, and audit committees on the company performance.